Детектор b-частинок на основі фулериту C60 - Забулонов, Ю.Л.; Лисиченко, Г.В.; Макарець, М.В. (Видавничий дім "Академперіодика" НАН України, 2007)
We propose to use fullerite C60 layers as a sensitive material for chemical detectors of b-particles. A model of the accumulation of new polymeric bonds between molecules and the amorphization of a layer under radiation is proposed. The estimations of the dependences of these characteristics on the absorbed dose of the irradiation by b-particles emitted by tritium are obtained.